Graphene Oxide-Modified Microcapsule Self-Healing System for 4D Printing - Ma, Bowen; Zhang, Yuping; Wei, Yongjie; Li, Mingrui; Li, Dongdong (Frontiers in Materials, 2021)
Self-healing materials as a type of promising smart materials are gradually applied to electronics, biology, and engineering. In this study, we used in situ polymerization to make melamine-formaldehyde (MF) resin microcapsules to wrap the epoxy oxide as a repairing agent and Cu(MI)4Br2 as a latent-curing agent to protect epoxy oxide E-51 from broken melamine-formaldehyde resin microcapsules. In addition, graphene oxide was used as a reinforcing phase through its two-dimensional-layered structure to increase the tensile strength to 41.91 MPa, which is higher than the initial materials. The melamine-formaldehyde capsules and latent-curing agents were uniformly distributed in the materials according to the digital photos and scanning electron microscope (SEM) pictures. It is worth noting that the mechanical strength of the broken materials can be restored to 35.65 MPa after heating to 130°C for 2 h to repair the damage, and the self-healing efficiency reached up to 85.06%. Furthermore, we also fabricated the 4D printed material with a tensile strength of 50.93 MPa through a 3D printer. The obtained materials showed excellent repair effect, with a recovery rate of up to 87.22%. This study confirms that the designed self-healing system has potential applications in many areas due to its excellent self-healing performance, which provides valuable guidance for designing the 4D system.